SELF-REGULATED LEARNING DALAM KEPEMIMPINAN MAHASISWA PENDIDIKAN ULAMA TARJIH MUHAMMADIYAH - Miqdad Tattaq Noto Sabdo Agus Suryanto (Al Ulya: Jurnal Pendidikan Islam, 2021)
This study aims to examine and analyze the Self Regulated Learning Education Student Scholars Tarjih Muhammadiyah Muhammadiyah University of Yogyakarta the End of the Level. This research is a field research using qualitative descriptive approach. The study subjects consisted of the mudir, lecturer, musrif/ah, and student/i PUTM. Data were collected through observation, interview, and documentation. Then the data were analyzed with the stages of reduction, presentation, and conclusion. The results of the study showed that the students can easily to customize yourself in environmental Education Scholars Tarjih Muhammadiyah, especially in the Unires both sons and daughters and each student has a different way so that students have self-regulation, which is not easily affected by external environment and influenced by friends, always have a regular schedule and words of motivation that always remind students on the purpose of the early learning in Educational Scholars Tarjih Muhammadiyah. Students have self-regulation is good because students also do the rules that exist in the Education of Scholars Tarjih Muhammadiyah done in their home when the holidays, so what do they get in the Education of Scholars Tarjih Muhammadiyah not in vain because they also do it at home